When Project Management Methods Collide - Sköld, Mildred; Dahlqvist, Sanna (My University, 2022)
The need for organizations to perform projects well has increased in today’s inter national, demanding, and ever-changing market. To manage projects, organizations can utilize different project management methods, where recently there has been a transition from traditional to agile project management methods (APM). It has however come to light that the use of APM has not always been successful and that there are situations where traditional methods would have been more favorable. Therefore, for organizations to remain competitive, a need to apply the most favor able method depending on the specific situation has arisen which has resulted in the coexistence of both agile and traditional methods within larger organizations, conducting projects in parallel. However, due to the different and oftentimes con trasting principles of different methods, i.e., – agile & traditional – challenges are likely to arise within such environments. The purpose of this thesis is thus to under stand when APM is more favorable compared to traditional methods. In addition, the thesis aims to identify potential challenges that could arise when agile and tra ditional methods are employed by different teams within an organization. A case study at Ericsson was conducted to discover challenges that can arise due to the coexistence of agile and traditional methods. In parallel, a literature study was performed to identify factors that indicate when agile was more favorable to apply. In the study, 21 factors divided into four categories – project, team, organizational & external – were identified to influence the favorableness of APM. Furthermore, the case study identified five challenges that could arise within an organization when different methods coexist. Conjointly, these challenges pose issues within the whole organization. In its entirety, this thesis provides practitioners with an overview of factors deemed to influence when APM is favorable along with outlining potential challenges that can occur in an environment where different project management methods are used in parallel and where these reside within an organization. All in all, this thesis facilitates a more thorough understanding of when APM is favorable and what challenges organizations that wish to apply different project management methods can anticipate while providing a basis for future research.
Keywords: agile; agile favorability; agile project management; challenges when methods collide; coordination challenges; traditional project management